An assessment of health and safety practices for employees at health care institutions within the city of Mersin - Gülden Ersöz; Ali Koray Kenziman; Hakkı Aktaş; Ahmet Öner Kurt (Turkish Society of Public Health Specialists, 2018)
Objective: The aim of this research was to assess employee health and safety practices, in public and private healthcare institutions providing services in the city of Mersin. Methods: The data of this descriptive study was collected through questionnaires conducted in September 2015. Thirty-four healthcare institutions in total were included for this work. These institutions have been providing second and third tier health services for the city center, as well as the surrounding districts of Mersin. Results: When assessed in terms of the number of employees in occupational health and work safety services, only 10.1% of health workers were found to have satisfactory access to occupational physicians, whereas only 0.8% received enough support from occupational health and safety experts. When the access to both the occupational physicians and the occupational health and safety experts were evaluated together, only 0.8% of the health workers were found to be able to receive adequate contact time. In 2014, 52.9% of the employees were examined periodically and 94.1% of the institutions had established risk assessments. Conclusion: In Mersin, only 1% of the health workers are provided with occupational health and work safety services for a sufficient period of time by occupational physicians and occupational health and safety experts. This has been highlighted as a major shortcoming.